Factors related to cardiac rupture after acute myocardial infarction - Gao, Xue; Guo, Ying; Zhu, Xiaoting; Du, Chunlei; Ma, Beibei; Cui, Yinghua; Wang, Shuai (Frontiers in Cardiovascular Medicine, 2024)
Cardiac rupture (CR) after acute myocardial infarction (AMI) is a fatal mechanical complication. Early identification of these factors in high-risk cases may reduce mortality. The purpose of our study was to discover relevant risk factors of CR after AMI and in-hospital mortality from CR. In this study, we enrolled 1699 cases of AMI from October 2013 to May 2020. A total of 51 cases were diagnosed as CR. Clinical diagnostic information was recorded and analyzed retrospectively. Randomly matched with AMI patients without CR in a 1:4 ratio. Univariate and multivariate logistic regression and stratifying analysis were utilized to identify risk factors for cardiac rupture. Univariate and multivariate Cox regression hazard analysis and stratifying analysis were used to assess predictors of in-hospital mortality from CR. The incidence of CR after AMI was 3.0%, and in-hospital mortality was approximately 57%. Multivariate logistic regression analysis identified white blood cell counts, neutrophil percentage, anterior myocardial infarction, Killip class > II, and albumin level were independently associated with CR (P<0.05). Stratifying analysis showed age, systolic blood pressure, and bicarbonate were independent risk factors for female CR (P<0.05) but not for male CR. Triglyceride, and cardiac troponin I were independent risk factors for male CR (P<0.05) but not for female CR. Anterior myocardial infarction, Killip class > II, and neutrophil percentage were independent risk factors for both male and female CR (P<0.05). Multivariate Cox regression analysis showed the time from Symptom to CR and site of CR were independent predictors for in-hospital mortality from CR (P<0.05). Stratification analysis indicated risk factors weren't gender difference, but platelet counts were predictors for in-hospital mortality among both female and male CR.Low albumin, high white blood cell counts and neutrophil percentage, anterior myocardial infarction, and Killip class > II were independent and significant predictors for CR. However, risk factors are different in male and female CR. The time from Symptom to CR, site of CR, and platelet counts were independent predictors for in-hospital mortality from CR. These may be helpful in the early and accurate identification of high-risk patients with CR and assess prognosis. Meanwhile, gender differences should be considered.